Populism and academic freedom - Rui Silva (Public Choice, 2026)
Abstract Academic freedom empowers scholars to influence public discourse and debate, cultivate critical reasoning, discuss ideas that challenge traditional values, and impose a soft check and balance on governments. For those reasons, governments have specific preferences regarding the extent of academic freedom, especially when led by populists, whose ideology, values, and strategic features are frequently at odds with the implications of this freedom. Using a quasi-experimental design, we confirm that academic freedom declines significantly under populist governments, a pattern largely independent of their host ideology. Those negative consequences increase after multiple populist terms, and extend more broadly to the substance of speech and the flow of information. Altogether, these results highlight the incompatibility of populism with democratic guarantees.